Pengaruh PEEP Terhadap CVP pada Pasien yang terpasang Ventillator Mekanik : Literatur Review - Djalil, Nia Kurnia Djalil; Sjattar, Elly L.Sjattar; Syahrul, Syahrul (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2020)
The purpose of this literature review is to discuss PEEP (Positive End Ekspiratory Pressure) and CVP (Central Venous Pressure) in patients who have ventilators. Adequate interpretation is needed by nurses who make direct observations about the patient's actual volume status without the influence of expiratory end pressure due to the administration of PEEP to patients who are attached to a ventilator. Study of this literature through a search of scientific publications using the database Pubmed, Google Scholar, Science Direct. Pubmed. Criteria for inclusion of this research article on PEEP and CVP in patients who are ventilators with publications between 2010-2017. This study shows that the effect of changing CVP values greatly influences hemodynamics and fluid status in the patient's body and determines the next interventions that will be given to patients so that changes in CVP values with PEEP in patients who are fitted with mechanical ventilators are needed in order to determine a meaningful CVP value. Based on this description, it is recommended that research studies related to changes in the conversion of CVP values with PEEP.